2013
DOI: 10.3748/wjg.v19.i26.4146
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Treg cell to Th17 cell ratio may alleviate HBV-related acute-on-chronic liver failure

Abstract: Restoring the Treg cell to Th17 cell ratio during the follow-up phase of ACLF could maintain the immune system at a steady state, which favours good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…In the mouse model of RSV infection, RSV‐induced immunopathology in the lung could be modulated by regulating the balance between Treg and Th17 cells . In HBV infection, restoration of the Treg/Th17 cell ratio was believed to be helpful for the maintenance of the immune homoeostasis and favouring good outcomes for patients with HBV‐related ACLF . Besides, the Treg/Th17 cell ratio can also be used as a potential marker for the prediction of the occurrence of decompensated liver cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse model of RSV infection, RSV‐induced immunopathology in the lung could be modulated by regulating the balance between Treg and Th17 cells . In HBV infection, restoration of the Treg/Th17 cell ratio was believed to be helpful for the maintenance of the immune homoeostasis and favouring good outcomes for patients with HBV‐related ACLF . Besides, the Treg/Th17 cell ratio can also be used as a potential marker for the prediction of the occurrence of decompensated liver cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…The Treg and Th17 cells participate in the progression of hepatic failure. Niu et al found that both circulating Treg and Th17 cell frequencies increased in hepatitis B virus- (HBV-) ACLF patients compared to the healthy ones [ 7 ]. However, others showed that the circulating Th17 cell proportion increased significantly and Treg cell changed without statistical significance [ 8 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together with Th17 cells, regulatory T cells (Tregs) play a major role in human disease . Accordingly, recent reports suggest that controlling the balance between Tregs and Th17 cells may be a promising therapeutic strategy for inflammatory diseases . However, no data are present in the literature about Tregs in PG.…”
mentioning
confidence: 99%